A New Approach to Underpricing Phenomenon in Poland - Podedworna-Tarnowska, Dorota (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis. The purpose of the article is to identify and assess the underpricing of initial public offerings in Poland on the regulated and alternative markets, considering the division of total underpricing into primary underpricing and secondary underpricing. The study also takes into account different types of IPOs (cold, neutral and hot). Such an approach to measuring underpricing based on the data coming from both the regulated market of the Warsaw Stock Exchange and the alternative market – NewConnect, is pioneering on the Polish market. Methodology. The statistical analysis covers 271 companies debuting on the regulated market of the Warsaw Stock Exchange between 2005 and 2022 and 585 companies debuting on the alternative market between 2007 and 2022. Total underpricing was divided into primary underpricing and secondary underpricing. All IPOs were split into cold, hot, and neutral offerings according to the secondary underpricing. T-tests for estimating the significance of the rate of returns were conducted for both the regulated and alternative markets. The correlations were estimated using Pearson’s index. Results of the research. The results of the analysis show that in Poland, the IPO underpricing occurring on the primary market is significantly positive, representing the remuneration of subscribers for participating in the initial public offering. Moreover, it is higher for an IPO on the alternative market than on the regulated market. In contrast, returns calculated from opening prices to closing prices on the first day of trading are negative in both markets, with lower returns in the NewConnect market. The average primary underpricing for cold IPOs is higher than for hot IPOs for both the regulated and alternative markets. Average secondary underpricing is negative for cold IPOs and positive for hot IPOs on both the regulated market and NewConnect. Furthermore, there is a significant positive correlation between primary and total underpricing regardless the hotness of the IPOs and a positive significant correlation between primary and secondary underpricing occurs only for hot offers while for cold offers it is negative.